ASSISTANCE FOR THE DEVELOPMENT OF LEARNING DEVICES USING THE CONSTRUCTIVISM MODEL WITH CAMTASIA STUDIO INTERACTIVE VIDEO MEDIA FOR TEACHERS - Sri Wahyuni; Jimi Ronald; Mona Amelia (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2021)
The constructivism method was chosen as an alternative in teaching because this method is considered an effective way to direct all potential students so that they are more motivated during the teaching and learning process which has a positive impact on their learning outcomes. Another problem with this online learning system is that access to information is constrained by signals that cause slow access to information. The application of online learning also makes educators think again about the learning models and methods that will be used. Initially, a teacher had prepared a learning model to be used, then had to change the learning model. Camtasia is a software from the Techsmith Corporation. This application is used to record activities on a computer desktop according to the wishes of the user, such as making video tutorials and presentations directly to Microsoft PowerPoint, so that teachers can create creative and innovative learning media. By using the Camtasia studio media, indirectly the ability to use and access technology is increasingly controlled by the teacher.